The Role of Regulation Schools in Preventing and Overcoming Bullying - Mulia, Lusi Tutur (CERED Indonesia Institute, 2024)
This research aims to analyze role regulation schools in preventing and overcoming bullying in the environment school. This research was conducted towards teachers, students and staff school that is done in a way random via google form. Data analysis techniques are carried out in a way qualitative approach? bibliography and studies literature. Based on results study Still Bullying actions were found in several school. Regulations clear, firm and implemented school? in a way consistent role? important in preventing and overcoming bullying. Regulations the give strong foundation? for school to handle bullying quickly and fairly, and? create safe environment? for all students. In addition, the approach involves all over community schools, including students, teachers, parents, and staff, are very supportive prevention bullying. Support for victims and recovery the perpetrator is also important to overcome bullying in a way comprehensive